Modelling of multi-dimensional loyalty in electronic commerce / Nader Sohrabi Safa - Safa, Nader Sohrabi (2014)

(untitled)
Advances in web-based oriented technologies and services are taking place with a considerable speed around the world. New technologies have significantly influenced trade, and converted traditional commerce to e-Commerce. Modern commerce enables people to conduct business in their offices or at homes, with minimal time, cost, error, and maximum efficiency. Customer trust, satisfaction and loyalty play vital roles in the success or failure of e-Commerce. It is also clear that loyal customers are one of the most important assets of firms, which results in long-term benefits. In this research, three problems were addressed. Firstly, companies easily lose their e-Customers in the competitive environment of today‘s business (Internet). Secondly, gaining loyal customers takes a long time, and is high in cost. Thirdly, there are inactive and nonprofitable customers in the database of online companies; converting inactive and nonprofitable customers to active and profitable customers by increasing their trust, satisfaction and loyalty. These three basic problems encourage us to study the nature of e-Loyalty formation in e-Commerce. The main aim of this study is to answer the question of how firms can increase Electronic Trust (e-Trust), Electronic Satisfaction (e-Satisfaction) and Electronic Loyalty (e-Loyalty) among their e-Customers. A review of literature and interviews with experts in this domain revealed that e-Satisfaction and e-Trust are two important factors that influence e-Loyalty. The significant aspect of this research is derived from the inclusion of a comprehensive conceptual framework with different aspects of technology, organization, and customers (three main entities in e-Commerce). Nine hypotheses display the relationships between technological, organizational, and customer factors with e-Satisfaction and e-Trust, which is significantly influence e- Loyalty. The data for this study were collected from e-Customers of the largest retail company in Iran in 2011, and statistical analyses were used to validate and ensure the reliability of the proposed model. The results showed the relationship between technological, organizational and customer factors with e-Satisfaction, e-Trust, and finally, e-Loyalty. The findings also revealed the fact that technological factor has the most effect on e-Satisfaction, e-Trust and e-Loyalty. Furthermore, Artificial Neural Fuzzy Interface System (ANFIS) was utilized to estimate e-Loyalty based on e- Satisfaction and e-Trust as assessment of the results. The outcomes showed a slight iii difference between the prediction of ANFIS and e-Loyalty data. The results of both methods (statistical analysis and ANFIS) confirm the reliability of the model. This research sheds some light on the formation of e-Loyalty in e-Commerce and can be useful for academics and practitioners.